National identity, mode of networking and integration of Bangladeshi community in a multi-cultural society: an empirical study among the migrant Bangladeshis in Peninsular Malaysia. - Nayeem Sultana (Universiti Kebangsaan Malaysia, 2007)
Sila rujuk teks penuh/ Please refer to full text